African trypanosome strategies for conquering new hosts and territories: the end of monophyly?. Issue 9 (September 2022) - Lukeš, Julius; Kachale, Ambar; Votýpka, Jan; Butenko, Anzhelika; Field, Mark C.
Abstract : Trypanosoma brucei parasites are the causative agents of African trypanosomiasis in humans, as well as surra, nagana, and dourine in animals. According to current widely used nomenclature, T. brucei is a group of five (sub)species, each causing a distinct disease and possessing unique genetic marker(s) or a combination thereof. However, minimal nuclear genome differences, sometimes accompanied by ongoing genetic exchange, robustly support polyphyly resulting from multiple independent origins of the (sub)species in nature. The ease of generating such (sub)species in the laboratory, as well as the case of overlapping hosts and disease symptoms, is incompatible with the current (sub)species paradigm, which implies a monophyletic origin. Here, we critically re-evaluate this concept, considering recent genome sequencing and experimental studies. We argue that ecotype should be used going forward as a significantly more accurate and appropriate designation. Highlights: Trypanosoma brucei is a complex of five ecotypes, namely, T. brucei f. brucei, T. b. f. gambiense, T. b. f. rhodesiense, T. b. f. equiperdum, and T. b. f. evansi, which are highly evolvable and appear to conquer new hosts and territories relatively easily as a result of just a few simple mutations in their genomes, which can be induced even in laboratory conditions. The subspecies status of T. brucei lineages is incompatible with the accumulating evidence pointing at the significant genetic similarities, apparent polyphyly, as well as overlapping hosts and disease symptoms. The ecotype concept fits the data accumulated in the area of African trypanosome research much better than the subspecies nomenclature.